Optimum micronutrient level for Phalaenopsis deliciosa orchid seedling in vitro growth - Xiong, Zherui; Choong, Chieh Wean (Science Publications, 2014)
There were many researches about the influence of micronutrient concentration toward growth of plants. However, there was no clear statement about the micronutrient level for growth of Phalaenopsis seedlings. Hence it was worth to investigate the optimum level of micronutrient for Phalaenopsis, an endangered orchid species. Using Phalaenopsis deliciosa as the subject, germinated seedlings were grown on defined culture media containing different MS micronutrient level. After 90 days with a subculture at day 45, fresh and dry weights of shoots and roots of the seedlings were measured. It was found that the optimum micronutrient level for P. deliciosa seedling growth was observed between 0.50× and 1.00× of MS micronutrient level. Higher micronutrient level caused roots and seedlings to deterioration except for a minority of seedling variants that grew exceptionally well, suggesting that high micronutrient level was selective for a small number of variants. The study demonstrated the importance of appropriate micronutrient level for supporting growth and development for wide range of genotypes in P. deliciosa. This micronutrient level may as well be optimum for other species under the genus Phalaenopsis and should be considered for maintaining genotype diversity in vitro.